ITIL 2011: The Maturity of IT Service Operation in Universitas Multimedia Nusantara, Indonesia - Michael Van Wis Lee; Wella Wella (IJNMT (International Journal of New Media Technology), 2018)
Information Technology governance (IT Governance) in the world of education is quite widely used including in Indonesia itself, for example at some educational institutes. The ITIL framework, used as a tool for evaluation, audit and also as a reference implementation. To help improve the Universitas Multimedia Nusantara (UMN) IT service in the service operation section, it is necessary to know the maturity level of the service, which is then done through the measurement of maturity level in the service operation section. In addition, the measurement results obtained can be used to produce the right recommendations with the problems found in the service. Measurements are made on the domain service operation which is the focus of UMN's IT department services. Service Operation has 5 indicators: incident management, problem management, access management, event management and request fulfillment. In this research, the framework used is ITIL Version 2011. The result of this measurement has been found: incident management, problem management, event management and request fulfillment get the result of measurement at level 1 and access management up to level 2. The result of measurement and recommendation given is expected to be input material and become development material that can be used by the IT department of Universitas Multimedia Nusantara.